Patient Safety and Clinical Risk Management for General Practice - Lucio Mango (International Journal of General Practice, 2020)
General practitioners are the first contact between the person, the family and the community with the health system. The philosopher and epistemologist K. Popper (1902-1994) recommended the need to register errors, in order to know them, catalog them and therefore prevent them. J.Reason in 1963 introduced the systemic approach to the study of errors with the theory of latent errors. The knowledge of the causal factors, or which in any case contribute, of possible errors, as well as of the latent gaps in the system, is a fundamental prerequisite for the construction of paths aimed at improving the quality of assistance, structures and organizational aspects.
Keywords: General practice